Nilai Perusahaan di Pasar Modal Indonesia: Analisis Struktur Modal, Profitabilitas, dan Ukuran Perusahaan - Dany Adi Saputra; Widowati Dian Permatasari (Indo Publishing, 2026)
This study aims to examine the effect of capital structure, profitability, firm size, and institutional ownership on firm value in public companies listed on the Indonesia Stock Exchange. The study uses a quantitative approach with secondary data obtained from financial statements and annual reports. The research sample was determined using a purposive sampling method and resulted in 166 observations. Data analysis was performed using multiple linear regression after the model met all classical assumption tests. The results show that capital structure, profitability, firm size, and institutional ownership simultaneously have a significant effect on firm value. Partially, capital structure and profitability have a positive and significant effect on firm value, while firm size and institutional ownership have no significant effect. These findings indicate that investors place more emphasis on a company's financial performance and financing policies than on its structural characteristics in assessing firm value. This study provides important implications for management in formulating financial policies and for investors in making investment decisions.